Levels and trends of maternal death in Baoan district, Shenzhen, China, 1999–2022 - Wang, Wei; Zhu, Yuanfang; Cheng, Yuli; Chen, Xu; Luo, Yali (Frontiers in Public Health, 2023)
Background China had achieved impressive success in improving maternal health, while the progress of reducing maternal mortality ratio (MMR) varied across regions. Some studies had reported maternal mortality from national or provincial perspective, but researches of the MMR on long-term period at the city or county level rare been reported. Shenzhen has experienced significant socioeconomic and health changes, reflecting the typical development of China's coastal city. This study mainly introduced the levels and trends of maternal death in Baoan district, Shenzhen from 1999 to 2022. Methods Maternal mortality data were extracted from registration forms and the Shenzhen Maternal and Child Health Management System. Linear-by-Linear Association tests were used to evaluate the trends of MMR among different groups. The study periods were divided into three stages by 8-year interval and χ2 test or Fisher's test was used to test the difference in maternal deaths of different periods. Results During 1999–2022, a total of 137 maternal deaths occurred in Baoan, the overall MMR was 15.91 per 100,000 live births, declined by 89.31% with an annualized rate of 9.26%. The MMR declined by 68.15% in migrant population, with an annualized rate of 5.07%, faster than that in permanent population (48.73%, 2.86%). The MMR due to direct and indirect obstetric causes shown a downward trend (P<0.001) and the gap between them narrowed to 14.29% during 2015–2022. The major causes of maternal deaths were obstetric hemorrhage (4.41 per 100,000 live births), amniotic fluid embolism (3.37 per 100,000 live births), medical complications (2.44 per 100,000 live births) and pregnancy-induced hypertension (1.97 per 100,000 live births), the MMR due to the above causes all shown decreasing trends (P < 0.01), pregnancy-induced hypertension became the leading cause of deaths during 2015–2022. The constituent ratio of maternal deaths with advanced age significantly increased by 57.78% in 2015–2022 compared with in 1999–2006. Conclusions Baoan district had made encouraging progress in improving maternal survival, especially in migrant population. To further reduce the MMR, strengthening professional training to improve the capacity of obstetricians and physicians, increasing the awareness and ability of self-help health care among elderly pregnant women were in urgent need.